Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis